Effect Of Giving Different Probiotic Doses On Fish Feed Toward The Growth And Survival Rate Of Gouramy Fish(Osphronemus gouramy) - Eko Prasetyo A.Y Putra; Rusliadi Rusliadi; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This reaserch was conducted from 26 October to 4 December 2018, at the laboratory of Aquaculture Technology, Faculty of Fisheries and Marine University Of Riau. The main purpose of this study was to determine the effect of different probiotic doses on fish feed toward the growth performance and survival rate of Gouramyfish (Osphronemus gouramy). The probiotic was used in this study was probiotic which is composed of Lactobacillus sp., Nitrosomonas sp. and Bacillus sp. This research used a Ccompletely Randomized Design (CRD) with one factor, five treatments and three replications. Doses of probiotic were used in this research were P0 (control), P1(5 ml/kg of feed), P2(10 ml/kg of feed), P3(15 ml/kg of feed) dan P4(20 ml/kg of feed).Result of this research gave significant effecttoward the absolut weight growth, absolut length growth and spesific growth rate,while for the feed efficiency, and survival ratenot gave significant effect on any treatments (P>0.05). The best treatment was on the addition probiotic dose 15 ml/kg of feed giving  4.59 g of absolut weigth growth, spesific growth rate was 2.45 g, feed efficiency was 27.62% g and survival rate was 93.33 %.Keyword: Pribiotic, Gouramy Fish, Growth, Survival Rate